DINAMIKA QIRĀ’AH FARSH AL-ḤURŪF DALAM TAFSĪR JALĀLAYN : Studi Analisis Morfologis dan Implikasinya - Rizqi Nuryah (STAI AL-ANWAR SARANG, 2023)
This article attempts to examine the influence of qirā'ah farsh al-ḥurūf on the interpretation of al-Suyūṭī in Tafsīr Jalālayn. This study is important because knowing the differences in meaning in a qirā'ah will prove that differences in the history of receiving qirā'ah can influence an interpretation or not. This research uses a descriptive-analytical method using morfologi theory to reveal differences in the meaning of interpretation so that it can be concluded: the inclusion of qirā'ah in the book Tafsīr Jalālayn surah Āli 'Imrān carried out by al-Suyūṭī is purely in accordance with his sanad qirā'ah in the book Sharḥ al-Shāṭibiyah, except verse 21, and the differences in qirā'āt in Tafsīr Jalālayn surah Āli 'Imrān influence the interpretation of the meaning but do not contradict each other.